PRELIMINARY PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL STUDIES OF THE LEAVES OF ECLIPTA ALBA (L) - VENKANNA LUNAVATH; ESTARI MAMIDALA (International Journal of Pharma and Bio Sciences, 2013)
Globally, medicinal plants have been used for treatment of several ailments. The present study was performed to evaluate anti microbial activity and preliminary phytochemical screening of Eclipta alba (L) leaf extracts. The Eclipta alba (L.) belongs family Asteraceae. The Eclipta alba were shade dried, powered and was extracted using solvents Methanol and other solvents. The antimicrobial activity test performed by the disc diffusion method. Preliminary phytochemical analysis of the plant extracts fractions of Carbon tetrachloride fraction (CTF), Chloroform fraction( CFF) and Aqueous fraction(AQF) showed the presence of alkaloaids, tannin, flavonoids phenolic group and flavonoids. The CTF fraction of E. alba showed high activity against E. coli and E. faecalis bacteria.